Pengaruh Perkembangan Ragam Bahasa terhadap Perkembangan Kognitif Anak di Era 4.0 - Panggabean, Alimatusakdia; Budiman, Budiman; Rahma, Alya (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Several language variations have drawn support and criticism over time. Concerns about the effects on children, especially those related to cognitive and linguistic characteristics, have emerged with the proliferation of children's educational institutions using the Language Variety program. Those opposing these claims say that children will experience speech delay, but some research has produced contradictory findings. The purpose of this literature review is to explore how children participating in the Language Variety program in their school and everyday environment develop cognitively.